1996
DOI: 10.1021/ie950223b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graft-Modified Porous Polymer Membranes

Abstract: Porous poly(vinylidene fluoride) membranes were graft modified with acrylic acid by radiation-induced grafting utilizing electron beam. When the grafted membranes were characterized by the measurements of convective permeability, diffusion, and ion exchange properties, the membranes showed properties of variable permeability membranes with respect to the permeability of solvent and the ionic semipermeability. The permeability for the studied membranes (extent of grafting varied from 0 to 93 wt %) can be contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…It has been experimentally observed that the hydraulic permeability of a poly(acrylic acid)-grafted porous poly(vinylidene fluoride) membrane changed by three orders of magnitude with pH, while the diffusional permeability changed by only a factor of 2.4. 4 Conformation changes of the graft polymer could have a stronger effect on hydraulic permeability because flow rate is proportional to the fourth power of the pore radius, 13 while diffusional rate is only proportional to the square of pore radius. 15 Some theoretical studies on ionizable polymer brushes have been conducted to correlate properties of the graft polymer chain, for example, brush height and degree of ionization, with the pH and ionic strength of the surrounding solution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally observed that the hydraulic permeability of a poly(acrylic acid)-grafted porous poly(vinylidene fluoride) membrane changed by three orders of magnitude with pH, while the diffusional permeability changed by only a factor of 2.4. 4 Conformation changes of the graft polymer could have a stronger effect on hydraulic permeability because flow rate is proportional to the fourth power of the pore radius, 13 while diffusional rate is only proportional to the square of pore radius. 15 Some theoretical studies on ionizable polymer brushes have been conducted to correlate properties of the graft polymer chain, for example, brush height and degree of ionization, with the pH and ionic strength of the surrounding solution.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been shown to control the reaction and to obtain high densities of surface-grafted polymer. 25 Several surface 'grafting from' techniques have been reported in the literature, including chemical grafting, 25 plasma, 24,26 radiation 13,19,27,28 and photoinduced grafting. 29,30 A previously reported plasma-induced grafting technique 24 was chosen for the grafting of PNIPAM to the PCTEPMs because it presented several advantages to incorporating the desired properties into the PC membrane.…”
Section: Synthesis Pathway To Incorporate Pnipam Into Pctepmsmentioning
confidence: 99%
“…13,26,30,38 Switching responses with a bigger change in pore sizes, from 50 to 200 nm, have been achieved using hydrogels; however, these systems present very long response times. 39 Permeability switching experiments in response to light The experimental setup and pore size calculations (Hagen-Poiseulle) used for the thermal switching experiments were also used for the light-induced permeability changes in the synthesized NPCgPCTEPMs (Figure 6a).…”
Section: Synthesis Pathway To Incorporate Pnipam Into Pctepmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These movable membranes are further coupled to magnetic, piezoelectric or pressure actuated methods which allow external switching. Some examples of mechanical actuators include permeable membranes (Hautojarvi et al, 1996;Kontturi et al, 1996;Ulbricht, 1996;Peng and Cheng, 1998;Peng and Cheng, 1999;Peng and Cheng, 2001;Chu et al, 2003;Gatimu et al, 2006), and nanofabricated reservoirs that act as constant sources of reagents (Groisman et al, 2005;Frevert et al, 2006;Keenan et al, 2006).…”
Section: Types Of Actuators That Control Flowmentioning
confidence: 99%